Implementasi Bimbingan Kelompok Sebagai Usaha Untuk Meningkatkan Prestasi Belajar Ipa Materi Pernapasan Pada Siswa Kelas VIII B SMP Negeri 1 Sawit Kabupaten Boyolali Semester Genap Tahun Pelajaran 2017/2018 - Widhiani Purwaningsih (Lembaga Penelitian dan Pendidikan Mandala, 2019)
The purpose of this study was to determine the implementation of group guidance as an effort to improve the science learning achievement of respiratory material in the class VIII B of Junior High School 1 Sawit, Boyolali at the second semester of 2017/2018 academic year. The research method used is Classroom Action Research. The independent variable is the implementation of group guidance. Science learning achievement is the dependent variable. The population is class VIII B of Junior High School 1 Sawit, Boyolali at the second semester 2017/2018 academic year. How to take samples with the value of student test and direct supervision of the learning process, from counseling guidance teachers and homeroom teachers. Research result. Based on the results of learning research after application with the group guidance method can improve from the initial conditions to the second cycle. There was an increase in the average value of 71.09 to 79.38, increasing by 8.29. The number of students completed from 11 to 28, from the value of 60 to 70, increasing by 10 points. The highest score of 90 to 95, increased by 5 points.